Market-based certification and management of non-timber forest products in Bhutan: Organic lemongrass oil, poverty reduction, and environmental sustainability - Karma Yangzom; Irmela Krug; Kesang Tshomo; Sununtar Setboonsarng (Asian Development Bank Institute (ADBI), 2008)
Sustainable management of non-timber forest products is a serious concern of many developing countries. This study documents an innovative undertaking involving the introduction of a market-based organic certification scheme to improve the resource management and processing of lemongrass in poor households in Eastern Bhutan. With its high potential for income generation, organic certification serves as a tool to help achieve the combined objectives of natural resource management and income generation for rural communities through the payment of premium prices and opening of access to export markets. The study shows that the organic certification has a direct impact on income generation of participating households (distillers, grass collectors, and firewood collectors) and can contribute directly to Millennium Development Goal 1 (MDG1) on income and hunger. However, the findings also show that the premium prices earned by distillers were yet to be translated into higher wages for grass collectors in organic production. With regard to MDG7, direct impacts are apparent in the increased participation of local people in the sustainable management of lemongrass resources, but there has been no improvement with regard to the high fuel wood consumption. Increased efforts must be put into the improvement of the overall production and efficiency of distillation to make organic certified oil from Bhutan competitive with that from neighboring countries. The study also shows organic certification contributing to MDG8 on global partnership for development and MDG3 on gender empowerment.
Keywords: Q27; Q12; O31; J16; 330